DETERMINATION OF THE ANGULAR ACCURACY WHEN SETTING OUT THE CENTERS OF BRIDGE PIERS: DETERMINATION OF THE ANGULAR ACCURACY WHEN SETTING OUT THE CENTERS OF BRIDGE PIERS - Stefanova, Ani (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
The article determines the angular accuracy when setting out the centers of bridge piers, based on a designed geodetic network where the location of the points on the shores is established to ensure the required setting out accuracy of all piers. Theoretical conclusions are carried out under the assumption that setting out of the piers is performed directly by linear-angular measurements from 2 reference points. Strict preliminary assessment is conducted on the accuracy of setting out the centers of bridge piers by measurements from 3 reference points.